2008
DOI: 10.1016/j.neuroimage.2007.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine-induced uncoupling of cerebral blood flow and oxygen metabolism: A calibrated BOLD fMRI study

Abstract: Although functional MRI (fMRI) based on blood oxygenation-level dependent (BOLD) signal changes is a sensitive tool for mapping brain activation, quantitative studies of the physiological effects of pharmacological agents using fMRI alone are difficult to interpret due to the complexities inherent in the BOLD response. Hypercapnia calibrated-BOLD methodology is potentially a more powerful physiological probe of brain function, providing measures of the changes in cerebral blood flow (CBF) and the cerebral meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
163
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(185 citation statements)
references
References 40 publications
(72 reference statements)
16
163
1
Order By: Relevance
“…Medication was applied in a double-blinded way. One capsule (caffeine 200 mg or placebo) was taken per os 30 min prior to the MR imaging in agreement with previous investigations (Mulderink et al, 2002;Liu et al, 2004;Behzadi and Liu, 2006;Perthen et al, 2008 Participants performed an n-back task, a wellestablished WM task in fMRI (for example, see metaanalysis in (Owen et al, 2005)). Briefly, a sequence of letters was presented visually on an MR compatible canvas in the MRI scanner.…”
Section: Wm Taskmentioning
confidence: 70%
See 1 more Smart Citation
“…Medication was applied in a double-blinded way. One capsule (caffeine 200 mg or placebo) was taken per os 30 min prior to the MR imaging in agreement with previous investigations (Mulderink et al, 2002;Liu et al, 2004;Behzadi and Liu, 2006;Perthen et al, 2008 Participants performed an n-back task, a wellestablished WM task in fMRI (for example, see metaanalysis in (Owen et al, 2005)). Briefly, a sequence of letters was presented visually on an MR compatible canvas in the MRI scanner.…”
Section: Wm Taskmentioning
confidence: 70%
“…The rare fMRI activation studies used simple perceptual tasks (i.e. auditory oddball, visual stimuli), and suggested the presence of a caffeine-mediated neurovascular uncoupling in young individuals characterized by a significant decrease of CBF with a concomitant increase of evoked (and possibly baseline) oxygen metabolism mainly in frontal areas (Perthen et al, 2008;Griffeth et al, 2011;Diukova et al, 2012). Two fMRI activation studies using a placebo-controlled design and working memory (WM) activation paradigms showed a caffeine-induced blood oxygen leveldependent (BOLD) increase in fronto-parietal areas and a decrease in the thalamus (Koppelstaetter et al, 2008;Klaassen et al, 2013) in young to middle-aged volunteers ranging from 25 to 61 years.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, caffeine decreased CBF by 35% with a non-significant þ 5% change in CMRO 2 . 94 Reductions of CBF by 15% accompanied by increases in CMRO 2 by 8% were observed after cortical spreading depression in rats. 95 Several functional activation studies indicate that CBF may be considerably above the level needed to support CMRO 2 during a variety of specific stimulus conditions.…”
Section: Uncoupling Of Cerebral Blood Flow and Cerebral Metabolic Ratmentioning
confidence: 92%
“…Caffeine, a non--selective adenosine receptor antagonist (Pelligrino et al, 2010), elicits: 1) neurostimulant effects, primarily via A1 receptors and the dopamine system (Ferre, 2008;Pelligrino et al, 2010); 2) cerebrovascular effects, primarily via A2A and A2B receptors located on blood vessels (Pelligrino et al, 2010); and 3) arousal enhancing effects, via A2A receptors and the histaminergic arousal system (Ferre, 2008); with tolerance thought to arise as the brain regulates its population of adenosine receptors to reach a new state of equilibrium in response to levels of caffeine chronically present in the body (Jacobson et al, 1996;Ralevic and Burnstock, 1998;Sousa et al, 2011). Studies have shown that administration of 200 --250 mg of caffeine results in reduced CBF (Addicott et al, 2009;Field et al, 2003;Laurienti et al, 2003;Liau et al, 2008;Mulderink et al, 2002;Perthen et al, 2008), possibly accompanied by a reduction in the baseline BOLD signal (during simple motor and visual tasks) (Chen and Parrish, 2009b;Perthen et al, 2008) and changes in the magnitude (Griffeth et al, 2011;Laurienti et al, 2002) and temporal dynamics of the BOLD response Liu et al, 2004;Rack--Gomer et al, 2009). Furthermore, increased CBF has been found during caffeine withdrawal (Addicott et al, 2009;Field et al, 2003).…”
Section: Introductionmentioning
confidence: 99%